Spontaneous Pneumothorax as an Atypical Presentation of Pulmonary Paracoccidioidomycosis: A Case Report with Emphasis on the Imaging Findings - Mariana Leite Pereira; Edson Marchiori; Gláucia Zanetti; Guilherme Abdalla; Nina Ventura; Carolina Pesce Lamas Constantino; Viviane Brandão; Pedro Martins; Rodrigo Canellas; Antonio Muccillo; Romulo Varella de Oliveira (Case Reports in Medicine)
We describe the case of a 45-year-old male with pulmonary paracoccidioidomycosis and spontaneous pneumothorax. The patient presented to the hospital with sudden and intense chest pain accompanied by dyspnea and had a six-month history of dry cough, weight loss, and progressive dyspnea on exertion. Chest X-ray showed a small right pneumothorax, bilateral nonhomogeneous opacities, and emphysematous areas in the lung base. Chest computed tomography showed consolidation in both lungs, with architectural distortion, nodules, interlobular septal thickening, and emphysema, in addition to the right pneumothorax. A lung biopsy revealed yeast consistent with Paracoccidioides brasiliensis. No drainage was needed, and the lung was re-expanded. The patient was treated with antifungal drugs, showed mild improvement, and was referred to outpatient care.